()-(2 R,3S)-DIHIDROKUERSETIN, SUATU PRODUK BIOTRANSFORMASI (-)-EPIKATEKIN OLEH JAMUR ENDOFIT Diaporthe sp. E - Andria Agusta (Research Center for Biology-Indonesian Institute of Sciences, 2009)
The endophytic fungus Diaporthe sp.E show a unique ability to biotransform (-)-epicatechin into (-)-(2R,3R,4R)-leucocyanidin in a semisynthetic medium. Extension of the incubation time gave a major product (-)-(2R,35)-dihydroquercetin which was identified by spectroscopic methods.